2018
DOI: 10.1111/ejn.13825
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations in glucose concentrations affect DNA methylation at Lrg1 in an ex vivo rat cortical slice model of preterm brain injury

Abstract: Preterm birth affects 5-18% of all babies and is associated with neurodevelopmental impairment and increased neuropsychiatric disease risk. Although preterm birth associates with differential DNA methylation at neurodevelopmental genes in buccal DNA, including leucine-rich alpha-2-glycoprotein 1 (LRG1), it is not known whether these differences also occur in the brain, or whether they persist. Thus, there is a need for animal models or in vitro systems in which to undertake longitudinal and mechanistic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Higher methylation of leucine-rich alpha-2-glycoprotein 1 (a protein associated with neurodevelopment), as well as upregulation of poly (ADP-ribose) polymerase-1 and NF-kB expression (associated with microglial activation) were associated with higher glucose concentrations. 27 28 In EPT infants, hyperglycaemia >8.3 mmol/L on the first day of life was associated with white matter reduction at term-equivalent age. 7 A meta-analysis concluded that neonatal hypoglycaemia was associated with visual-motor impairments, thus implying a possible effect of hyperglycaemia on motor development.…”
Section: Discussionmentioning
confidence: 94%
“…Higher methylation of leucine-rich alpha-2-glycoprotein 1 (a protein associated with neurodevelopment), as well as upregulation of poly (ADP-ribose) polymerase-1 and NF-kB expression (associated with microglial activation) were associated with higher glucose concentrations. 27 28 In EPT infants, hyperglycaemia >8.3 mmol/L on the first day of life was associated with white matter reduction at term-equivalent age. 7 A meta-analysis concluded that neonatal hypoglycaemia was associated with visual-motor impairments, thus implying a possible effect of hyperglycaemia on motor development.…”
Section: Discussionmentioning
confidence: 94%
“…LRG1 got more superior performance than interleukin-6 in the prediction for inflammatory diseases of the central nervous system (Chong et al, 2018). Cartier et al (2018) Hippocampal LRG1 overexpression contributed to fewer synaptic vesicles and junctions, which led to memory impairment with increased age (Akiba et al, 2017). Three protein expression LRG1, secretoglobin family 3A member 1, and peptidoglycan recognition protein one were mainly associated with inflammation and apoptosis and they regulated the regeneration of nerves (Zheng et al, 2019).…”
Section: Part Five: Lrg1 Involved In Eye Diseasesmentioning
confidence: 99%
“…Considering the mother is the sole source of nutrition during this time, nutritional deficits could confound any findings in this model. Indeed, we have previously shown that extended periods of maternal separation in rats results in hypoglycaemia [32], which is independently associated with impaired neurodevelopment [33]. Further, traditional maternal separation models may not accurately recapitulate some of the common stressors associated with the NICU, including frequent handling and sleep deprivation.…”
Section: Introductionmentioning
confidence: 99%